A wear map of bearing steel lubricated by silver films - Yang, SH; Kong, H; Yoon, ES; Kim, DE (ELSEVIER SCIENCE SA, 2003)
Wear map of bearing steel lubricated by silver film has been constructed to delineate the wear transition behavior with the change in operating conditions. Experiments were performed in dry sliding conditions using two types of ball-on-disk type test rigs under the contact pressure of 100-1000 MPa and the sliding speed of 20-1000 mm/s in ambient air. For the silver coating, an ultra thin IBAD silver bond layer was firstly deposited on AISI 52100 steel surfaces and then a relatively soft silver film was deposited by a thermal evaporation method onto the first layer. This functionally gradient film showed a great improvement in the life, mainly owing to the better bond strength. In order to build up a general framework on the tribological behavior of the functionally gradient silver films, all test data were plotted on a map whose axes are contact pressure and sliding speed. As a result, three main regimes were clearly identified: (i) elastic/plastic deformation of silver coating without failure, (ii) mild wear regime after initial failure of silver coating and (iii) severe wear regime. In the mild wear regime, the contact surfaces were covered with transfer layers of agglomerated wear particles. The transfer layer acted as a protective layer and resulted in low friction after initial failure of the coating. The formation of transfer layer was suppressed by several destructive actions, when the sliding speed was high. And, above a critical sliding speed, no transfer layer was able to form. In the discussion, an empirical model that could explain the existence of critical sliding speed was proposed. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: DISCONTINUOUS TRANSFER FILMS; DUCTILE MATERIALS; GENERAL-APPROACH; SLIDING WEAR; ALLOYS; LAYERS